Dog–Human Relationships: Behavior, Physiology, and Wellbeing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This special issue contains 22 papers (20 research articles and two reviews) on dogs interacting with humans in many different environments, including animal shelters, homes, healthcare facilities, other work sites, and outdoor areas. Given these diverse settings, there are papers concerning interactions between people and shelter dogs, pet dogs, therapy dogs, service dogs, working dogs, and free-living dogs. The aim of this special issue is to inform how such interactions affect both canine and human behavior, physiology, and wellbeing. These papers will interest researchers in the field of Human-Animal Interactions (HAI), veterinarians, animal shelter administrators and staff, as well as people training and handling therapy, service, and working dogs.